COMPARISON OF EFFICACY OF ORAL AZITHROMYCIN PLUS TOPICAL BENZYL PEROXIDE VERSUS ORAL DOXYCYCLINE PLUS TOPICAL BENZYL PEROXIDE IN TREATMENT OF ACNE VULGARIS - AMIN, S; KHAN, MR; SALEEM, M; KHAN, A; MUSHTAQ, F (Biological and Clinical Sciences Research Journal, 2024)
Acne vulgaris is a common dermatological condition that impacts psychological well-being and social interactions. Despite numerous treatment modalities, the comparative efficacy of combination therapies involving oral antibiotics and topical agents remains inadequately explored. Objective: To compare the efficacy of oral azithromycin plus topical benzyl peroxide versus oral doxycycline plus topical benzyl peroxide in treating Acne vulgaris. Methods: This randomized controlled trial was conducted in the Department of Dermatology at PIMS, Islamabad, from July 2023 to December 2023, following ethical approval. A total of 190 individuals with Acne vulgaris were enrolled and divided into two groups through block randomization. Group A received oral azithromycin 500 mg once daily for three consecutive days each week combined with daily topical benzyl peroxide 5% gel for 12 weeks. Group B was treated with oral doxycycline 100 mg daily and daily topical benzyl peroxide 5% gel for the same duration. Treatment efficacy was assessed after 12 weeks based on lesion clearance, categorized as Excellent, Good, Moderate, Mild, or No Response. Statistical analysis was conducted using SPSS Version 26 to evaluate the differences in treatment outcomes between the groups. Results: Participants had a mean age of 23.88±8.06 years, with gender distribution of 32 males (33.7%) and 63 females (66.3%) in Group A, and 41 males (43.2%) and 54 females (56.8%) in Group B. Treatment responses were significantly better in Group B, with 17.9% achieving an excellent response and 46.3% a good response, compared to 6.3% and 28.4% respectively in Group A (p=0.001). Conclusion: The study concluded that both combinations of oral antibiotics and topical benzyl peroxide effectively manage Acne vulgaris. However, combining oral doxycycline with topical benzyl peroxide was significantly more effective than oral azithromycin with topical benzyl peroxide, achieving higher rates of excellent and good responses, greater reduction in acne severity, and fewer cases of no response.